The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1037/pac0000395
|View full text |Cite
|
Sign up to set email alerts
|

Wedialog.Net: A quantitative field test of the effects of online intergroup dialogue in promoting justice- versus harmony-oriented outcomes in Bosnia and Serbia.

Abstract: Online dialogue has tremendous potential to influence intergroup relations in conflict-ridden societies. Although prior research has identified intergroup harmony and justice as two distinct approaches to intergroup contact, little is known about whether online dialogue would foster a harmony-or justiceoriented discourse around conflict. To examine this question, the present study implemented a pre-post within-subjects design around a 4-week online dialogue intervention with Bosniaks and Serbs in the postconfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…While earlier contact and dialogue studies were mainly conducted in face-to-face settings, more recent studies describe interventions that are based on online intergroup communication (Amichai-Hamburger et al, 2015; Hasler & Amichai-Hamburger, 2013). In the research literature, these relatively new forms of intergroup communication are referred to, inter alia, as online intergroup dialogue (Mor et al, 2016; Selvanathan et al, 2019). Online intergroup dialogues are discussed in recent research in the context of intergroup contact theory and have been found to display patterns of communication that have also emerged as characterizing intergroup dialogue in face-to-face settings (Amichai-Hamburger et al, 2015; Mor et al, 2016; Selvanathan et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…While earlier contact and dialogue studies were mainly conducted in face-to-face settings, more recent studies describe interventions that are based on online intergroup communication (Amichai-Hamburger et al, 2015; Hasler & Amichai-Hamburger, 2013). In the research literature, these relatively new forms of intergroup communication are referred to, inter alia, as online intergroup dialogue (Mor et al, 2016; Selvanathan et al, 2019). Online intergroup dialogues are discussed in recent research in the context of intergroup contact theory and have been found to display patterns of communication that have also emerged as characterizing intergroup dialogue in face-to-face settings (Amichai-Hamburger et al, 2015; Mor et al, 2016; Selvanathan et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the research literature, these relatively new forms of intergroup communication are referred to, inter alia, as online intergroup dialogue (Mor et al, 2016; Selvanathan et al, 2019). Online intergroup dialogues are discussed in recent research in the context of intergroup contact theory and have been found to display patterns of communication that have also emerged as characterizing intergroup dialogue in face-to-face settings (Amichai-Hamburger et al, 2015; Mor et al, 2016; Selvanathan et al, 2019). More specifically, patterns that characterize processes of face-to-face dialogue (such as the gap in expectations of both parties regarding the topics of the dialogue as described in the above case of Jewish–Palestinian women’s encounters) were also found to characterize processes of online intergroup dialogue (Mor et al, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although the characteristics of the ideal democratic citizen have been neglected, psychologists have extensively examined the conditions in which the members of different groups can achieve more constructive and democratic relationships. The first two empirical studies by Mana (2019) and Selvanathan et al (2019) included in this issue of the journal examine the conditions of intergroup contact. These studies build on the extensive research being undertaken on contact and intergroup relations (including a special issue on contact research in this journal, volume 23, number 3, 2017), and offer hope that innovations in school contexts and the use of online intergroup dialogue can improve intergroup relations.…”
mentioning
confidence: 99%